Unique considerations in the assessment of ADHD in college students. Issue 4 (21st April 2021) - Lefler, Elizabeth K.; Flory, Kate; Canu, Will H.; Willcutt, Erik G.; Hartung, Cynthia M.
ABSTRACT: Evidence-based practice in psychology (EBPP) has long focused on treatment, but evidence-based psychological assessment (EBPA) is also crucial given the important role of accurate and reliable diagnostic practices in treatment planning. In terms of the diagnosis of attention-deficit/hyperactivity disorder (ADHD), EBPA practices are well-established for children, and more recently for adults, but for college students in particular there are special considerations that warrant attention. College students with symptoms of ADHD have some challenges that are unique, and thus the assessment and diagnosis of ADHD in these students is unique. The aim of this review is not to cover all EBPA strategies for diagnosing ADHD in emerging adult college students; rather, we will focus on the unique considerations at play in college ADHD assessment . These include (a) conceptual matters such as the appropriateness of the DSM-5 criteria for college students, the limitations of our understanding of ADHD this population because of a lack of diversity in research studies, and the issue of late-identified ADHD; and (b) practical matters, such as specific documentation needs, how to gather and interpret self- and other-report of symptoms, how to assess impairment, and alternate explanations for ADHD-like symptoms in college students.